Strategic Leadership Effects on Sustainable Organizational Performance of State Corporations in Kenya: The Mediating Influence of Digitalisation - Odhiambo, Kennedy; Aosa, Evans; Angima, Caren; Wainanina, Githii (European Journal of Business and Strategic Management, 2025)
Purpose: Rapid disruptions in the technological environment in the last two decades have occasioned the digitalisation phenomenon which is fundamentally redefining the strategic leadership, operations and performance of organizations. Digitalization is currently not well integrated in strategic leadership literature. Additionally, there is limited empirical evidence regarding the influence of digitalization on the nexus between strategic leadership and sustainable organizational performance especially in the context of public sector organizations in developing countries. Consequently, this study attempted to address these knowledge and contextual gaps inherent in literature, by investigating the influence of the digitalisation phenomenon on the relationship between strategic leadership and the sustainable performance of State Corporations in Kenya. Methodology: This empirical study was based on a positivistic research philosophy and involved a census survey of all the 250 State Corporations in Kenya. Primary data was collected using a self-administered structured questionnaire based on a Five point Likert scale. The quantitative data collected was subjected to both descriptive and inferential statistics based on linear regression analysis. Finally, the hypotheses stated were tested using Model 4 of Hayes process macros running on SPSS. Findings: Three key findings in respect to State Corporations can be gleaned from the study. First, strategic leadership significantly positively influenced digitalization. Second, had a positive and significant influence on sustainable organizational performance. Third, digitalization significantly partially mediated the relationship between strategic leadership and organizational performance. Unique Contribution to Theory, Practice and Policy: The study has important implications at three levels. First, it contributes to theory refinement by testing the predictions of the two theories undergirding its conceptualisation. Second, it provides useful insights and information that will assist policy formulation in public sector organizations relating to strategic leadership, digitalization and sustainable organizational performance. Finally, the study findings are bound to assist management practitioners to effectively create linkages among strategic leadership, digitalization and sustainable organizational performance which is often considered a challenge in public sector organizations.